ANALISIS IMPLEMENTASI RENCANA STRATEGIS SEKOLAH SEBAGAI UPAYA MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH PENGGERAK - Yuza, Arlina; Fitri Mulyana; Dini Susanti; Ade Sri Madona; Darwianis (Cerdas Proklamator, 2024)
This study aims to analyze the preparation, analyze the implementation strategy, and analyze the evaluation and implications of the implementation of strategic planning on the quality of education at SD Negeri 11 Lubuk Buaya Padang City. The type of research is qualitative research with a phenomenological approach, with observation, interview and documentation techniques. The results showed that the preparation of strategic planning in improving the quality of education, namely: a) analysis of the internal and external environment, b) strategy formulation with the formulation fully carried out by the team. At the implementation stage of strategic planning, the techniques or strategies used are: a) involving stakeholders by announcing the program at the beginning of the learning year, holding coordination meetings every month, assigning tasks according to their fields; b) maximizing the resources owned by budgeting program implementation costs and using existing facilities and infrastructure. At the evaluation stage, the evaluation carried out is internal and external evaluation. The implications of the implementation of strategic planning are an increase in the quality of education with indicators: a) improving the KBM process; b) increasing achievements; c) increasing the number of students d) increasing the percentage of graduation; e) the fulfillment of facilities supporting the learning process in accordance with SNP. Translated with DeepL.com (free version)